Menghadapi Tantangan Modernisasi Dengan Mewujudkan Kualitas Manusia Indonesia Melalui Peneguhan Pendidikan Moral - Asep Mahfudz (Universitas Negeri Malang, 2016)
Moral education is salient to promote the quality of the Indonesian man in facing the modernization in this era of information and globalization. Furthermore, this article describes more specifically the parameters of self-actualization in line with the Al Qur'an and its realization in the form of development through more concrete steps and educational approaches. The last part of this article discusses some essential points in order to invigorate the moral education in the future and in turn to equalize the effort in mastering science and technology.